Insulin Facilitates the Recovery of Myocardial Contractility and Conduction during Cardiac Compression in Rabbits with Bupivacaine-Induced Cardiovascular Collapse - Solmon Yang; Tserendorj Uugangerel; In-ki Jang; Hyung-chul Lee; Jong Min Kim; Byeong-Cheol Kang; Chong Soo Kim; Kook-Hyun Lee (Anesthesiology Research and Practice)
Bupivacaine inhibits cardiac conduction and contractility. Insulin enhances cardiac repolarization and myocardial contractility. We hypothesizes that insulin therapy would be effective in resuscitating bupivacaine-induced cardiac toxicity in rabbits. Twelve rabbits were tracheally intubated and midline sternotomy was performed under general anesthesia. Cardiovascular collapse (CVC) was induced by an IV bolus injection of bupivacaine 10 mg/kg. The rabbits were treated with either saline (control) or insulin injection, administered as a 2 U/kg bolus. Internal cardiac massage was performed until the return of spontaneous circulation (ROSC) and the time to the return of sinus rhythm (ROSR) was also noted in both groups. Arterial blood pressure, and electrocardiography were continuously monitored for 30 min and plasma bupivacaine concentrations at every 5 min. The ROSC, ROSR and normalization of QRS duration were attained faster in the insulin-treated group than in the control group. At the ROSC, there was a significant difference in bupivacaine concentration between two groups. Insulin facilitates the return of myocardial contractility and conduction from bupivacaine-induced CVC in rabbits. However, recovery of cardiac conduction is dependent mainly on the change of plasma bupivacaine concentrations.